Genetic Variability of Nile Tilapia Strains as Determined by Microsatellite DNA Markers. (24th June 2021) - Thomas, Brandylyn L.; Gomelsky, Boris; Delomas, Thomas A.; Novelo, Noel D.
Abstract: The main purpose of the present study was to investigate the genetic variability of Nile Tilapia Oreochromis niloticus strains by using microsatellite DNA markers and to compare these data with those previously obtained with single‐nucleotide polymorphisms (SNPs). Five mixed‐sex strains and four YY‐male strains were analyzed. All nine microsatellite loci were polymorphic; the number of unique alleles per locus varied from 6 at UNH216 to 33 at UNH880 . Strong correspondence was observed between the level of expected heterozygosity ( He ) or observed heterozygosity and the number of alleles per locus ( A ) or the number of private alleles. Strains with high levels of heterozygosity typically had higher values of A and the presence of private alleles. In general, mixed‐sex strains had higher genetic variability than YY‐male strains. Four mixed‐sex strains (GIFT, Ismailia Canal, LSA hybrid, and Miami) had the highest level of genetic variability, with mean He ranging from 0.630 to 0.798 and mean A ranging from 5.11 to 9.78. Three YY‐male strains (Fishgen YY Dark–Group 2, Fishgen YY Red, and Til‐Aqua YY) had low genetic variability, with mean He ranging from 0.282 to 0.367 and mean A ranging from 1.89 to 3.56. All investigated strains demonstrated low values of the inbreeding coefficient F IS (from –0.266 to 0.014), suggesting that mating of closely related individuals is being avoided during maintenance of these strains. Pairwise genetic differentiation index F ST values had a broad range (from 0.0915 to 0.6063), indicating different levels of genetic differentiation between strains. A dendrogram constructed according to shared allele distance showed the existence of two distinct clusters among strains. The present data on genetic variability of Nile Tilapia strains demonstrated substantial similarity with data from a previous study of SNPs in the same populations.